State feedback control of advanced static var compensator using a five-level NPC inverter topology - Mansour Benyamina; Ali Tahri; Abdelkader Boukortt (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper deals with the modeling and control of an advanced static var compensator (ASVC) using a five-level neutral point-clamped (NPC) voltage source inverter (VSI). The nonlinear state space model of the five-level ASVC is obtained from the d-q axis frame. The effectiveness of this compensator highly depends on the choice of the control strategy. The proposed state feedback control (SFC) technique is applied to adjust the ASVC Var flow with the AC transmission network and achieve DC voltage capacitor balance. The dynamic performance of the ASVC based SFC controller is evaluated under several operating conditions. The simulation results demonstrate that the proposed SFC control strategy is highly robust compared to the conventional Proportional-Integral (PI) control.